Design and experimental analysis of a novel slant‐plate photoreactor. Issue 2 (1st September 2022) - Zhao, Jianyong; Ren, Guangmin; Li, Zizhen; Meng, Xiangchao
Abstract: A novel slant‐plate photoreactor (SPR) immobilized with titanium dioxide (P25) was developed to address the disadvantage that the effluent on the backlight side of the corrugated plate photoreactor could not be treated. The SPR was tested and analyzed regarding the degradation of phenol under UV light. For comparison, a flat‐plate photoreactor, a slurry photoreactor, and a corrugated plate photoreactor were also examined. The performance of SPR in phenol degradation was higher than either corrugated plate photoreactor with the same angle or flat‐plate. Furthermore, SPR exhibited highest energy utilization efficiency compared to the corrugated plate photoreactor with the same angle and flat‐plate photoreactor in phenol oxidation. The superior performance of SPR was due primarily to the highly exposed catalyst surface area, high mass transfer coefficient, and multiple reuses of reflected light. In addition, the SPR was tested under natural solar light for its possible implementation in practice.